A scoping review to identify strategies that work to prevent four important occupational diseases. Issue 6 (29th March 2020) - Keefe, Anya R.; Demers, Paul A.; Neis, Barbara; Arrandale, Victoria H.; Davies, Hugh W.; Gao, Zhiwei; Hedges, Kevin; Holness, D. Linn; Koehoorn, Mieke; Stock, Susan R.; Bornstein, Stephen
Abstract: Background: Despite being largely preventable, many occupational diseases continue to be highly prevalent and extremely costly. Effective strategies are required to reduce their human, economic, and social impacts. Methods: To better understand which approaches are most likely to lead to progress in preventing noise‐related hearing loss, occupational contact dermatitis, occupational cancers, and occupational asthma, we undertook a scoping review and consulted with a number of key informants. Results: We examined a total of 404 articles and found that various types of interventions are reported to contribute to occupational disease prevention but each has its limitations and each is often insufficient on its own. Our principal findings included: legislation and regulations can be an effective means of primary prevention, but their impact depends on both the nature of the regulations and the degree of enforcement; measures across the hierarchy of controls can reduce the risk of some of these diseases and reduce exposures; monitoring, surveillance, and screening are effective prevention tools and for evaluating the impact of legislative/policy change; the effect of education and training is context‐dependent and influenced by the manner of delivery; and, multifaceted interventions are often more effective than ones consisting of a single activity. Conclusions: This scoping review identifies occupational disease prevention strategies worthy of further exploration by decisionmakers and stakeholders and of future systematic evaluation by researchers. It also identified important gaps, including a lack of studies of precarious workers and the need for more studies that rigorously evaluate the effectiveness of interventions.